Production of Poly-3-Hydroxybutyrate (Phb) Nanoparticles Using Grape Residues as the Sole Carbon Source - Vilos-Ortiz, C (Elsevier B.V., 2024)
The production of poly-3-hydroxybutyrate (PHB) on an industrial scale remains a major challenge due to its higher production cost compared to petroleum-based plastics. As a result, it is necessary to develop efficient fermentative processes using low-cost substrates and identify high-value-added applications where biodegradability and biocompatibility properties are of fundamental importance. In this study, grape residues, mainly grape skins, were used as the sole carbon source in Azotobacter vinelandii OP cultures for PHB production and subsequent nanoparticle synthesis based on the extracted polymer. The grape residue pretreatment showed a high rate of conversion into reducing sugars (fructose and glucose), achieving up to 43.3 % w w−1 without the use of acid or external heat. The cultures were grown in shake flasks, obtaining a biomass concentration of 2.9 g L−1 and a PHB accumulation of up to 37.7 % w w−1. PHB was characterized using techniques such as Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). The formation of emulsified PHB nanoparticles showed high stability, with a particle size between 210 and 240 nm and a zeta potential between −12 and − 15 mV over 72 h. Owing to these properties, the produced PHB nanoparticles hold significant potential for applications in drug delivery. © 2024 Elsevier B.V.